2004
DOI: 10.2465/jmps.99.180
|View full text |Cite
|
Sign up to set email alerts
|

Zircon growth in UHT leucosome: constraints from zircon-garnet rare earth elements (REE) relations in Napier Complex, East Antarctica

Abstract: Feldspathic leucosomes occur in an ultrahigh temperature (UHT) metamorphosed garnet bearing paragneiss/ quartzite in the Napier Complex, East Antarctica. Coarse (200 400 μ m) zircon grains occurring in the leucosomes display 3 textural domains: (I) dark CL (cathodoluminescence) structured inner core, (II) bright CL structured outer core, and (III) dark CL structureless rim. Chemical compositions, especially chondrite normalized REE patterns obtained by SIMS analysis, correlate with these three domains: the inn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
90
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 125 publications
(105 citation statements)
references
References 15 publications
12
90
0
3
Order By: Relevance
“…Loock et aI., 1990). The flat HREE pattern of the garnets is consistent with their lower crustal derivation; the increase in the Gd/Dy ratio has been previously interpreted as being controlled by load pressure (Bea et aI., 1997) or zircon/garnet partitioning (Whitehouse and Platt� 2003;Hokada and Harley, 2004). It is interesting to note that all analyzed garnets have MREE (pr, N d, Srn) contents higher than chondrite levels, also in agreement with the scarce previous data on felsic granulitic xenoliths (Reid, 1990).…”
Section: Methodssupporting
confidence: 89%
“…Loock et aI., 1990). The flat HREE pattern of the garnets is consistent with their lower crustal derivation; the increase in the Gd/Dy ratio has been previously interpreted as being controlled by load pressure (Bea et aI., 1997) or zircon/garnet partitioning (Whitehouse and Platt� 2003;Hokada and Harley, 2004). It is interesting to note that all analyzed garnets have MREE (pr, N d, Srn) contents higher than chondrite levels, also in agreement with the scarce previous data on felsic granulitic xenoliths (Reid, 1990).…”
Section: Methodssupporting
confidence: 89%
“…The Napier Complex contains felsic igneous precursors to orthogneisses as old as~3800 Ma, and most lithologies were formed or metamorphosed during the late Archean, but the timing of peak UHT metamorphism is controversial (Horie et al, 2012, and references therein). Some geochronological works suggested that the UHT metamorphism occurred no earlier than 2840 Ma, and possibly from 2590 to 2550 Ma (e.g., Harley et al, 2001;Crowe et al, 2002;Kelly and Harley, 2005), whereas other researchers interpret the younger~2500-2450 Ma age to represent the UHT event (e.g., Grew, 1998;Carson et al, 2002;Hokada et al, 2003;Hokada and Harley, 2004). The Rayner Complex was affected by amphibolite-to granulite-facies metamorphism between~990 and~900 Ma (e.g., Sheraton et al, 1987; Shiraishi et al, 1997;Harley, 2003).…”
Section: Regional Geologymentioning
confidence: 99%
“…Color version is available online from http://doi.org/10.2465/jmps.160128. Harley et al, 2001, submitted) and Mt Riiser-Larsen (R23; Hokada and Harley, 2004) and individual concordant zircon age-Ti data from the pelite 49643, described in this study (orange diamonds). The grey curve represents a T-time that suggests the persistence of UHT for 80-90 Myr based on the leucosome data.…”
Section: Slow Archaean Uht: the Napier Complex East Antarcticamentioning
confidence: 99%
“…Similarly, zircon U-Pb age data compiled for anatectic leucosomes and migmatitic gneisses from the Napier Complex (Fig. 6: Carson et al, 2002;Hokada and Harley, 2004;Kelly and Harley, 2005;Horie et al, 2012) shows at least four crystallisation 'events' from perhaps 2585 Ma through to 2510 ma and even 2490 Ma. Again, rather than invoking T fluctuations it is conceivable that local melt / wall rock interactions governed zircon crystallisation under UHT conditions.…”
Section: Constraining Temperature and Time In Uht Metamorphismmentioning
confidence: 99%
See 1 more Smart Citation